Proinflammatory humoral factors and their role in the pathogenesis of left ventricular hypertrophy in hypertension (literature review) - Myloslavskyi, Dmytro; Koval, Sergiy; Mysnychenko, Olga; Lytvynova, Olga; Shcheniavska, Olena (ScienceRise: Medical Science, 2026)
The aim of the research was to consider the role of chronic low-grade systemic inflammation and a list of pro-inflammatory factors (interleukins, chemokines, tumor necrosis factor alpha, adipocytokines, metalloproteinases and their inhibitors, growth and inflammatory factors, etc.) as predictors of the onset and progression of left ventricular hypertrophy and myocardial fibrosis in individuals with hypertension Materials and Methods: keywords search of native and foreign sources of literature from scientometric databases Google Scholar, Clarivate, Web of Science, Scopus, PubMed and its analysis, considering data from modern European and Ukrainian guidelines of recent years was performed. Results and Discussion. Data on the conditional classification of pro-inflammatory and anti-inflammatory cytokines, their activity in hypertensive heart and diastolic dysfunction, a number of traditional pro-inflammatory factors from the superfamilies of interleukins, pentraxins and transforming growth factor beta 1 are considered, as well as new promising biomolecules that are used as indicators of chronic low-grade systemic inflammation, including the experiments on hypertensive animals. The question of the prospects of using a multi-indicator model of pro-inflammatory factors in individuals with arterial hypertension is considered, a brief description of promising targeted therapeutic approaches to inhibit pro-inflammatory mechanisms in patients with is given. Conclusions. In the research works of the last 10 years, a high scientific interest in the pathogenetically significant role of chronic low-grade systemic inflammation, pro-inflammatory factors in the occurrence and progression of hypertensive heart disease and left ventricular hypertrophy has revealed, and the promise of using biomarkers as their indicators for further personalized treatment on this basis for this category of patients has proven